Histopathological findings in canine dirofilariosis - KALDRYMIDOU (Ε. ΚΑΛΔΡΥΜΙΔΟΥ) E.; PSYCHAS (Β. ΨΥΧΑΣ) B.; POUTAHIDIS (Θ. ΠΟΥΤΑΧΙΔΗΣ) Th.; PAPAIOANNOU (Ν. ΠΑΠΑΪΩΑΝΝΟΥ) N.; POLIZOPOULOU (Ζ. ΠΟΛΥΖΟΠΟΥΛΟΥ) Z. (Journal of the Hellenic Veterinary Medical Society, 2018)
The lesions found in ten dogs with severe chronic dirofilariosis were studied. In the lungs, the most significant changes were observed in the endarterium of the pulmonary artery branches. Also, remarkable were the vascular thrombosis and the granulomatous inflammatory response of the pulmonary parenchyma. The presence of severe granulomatous inflammation in the endarterium of the pulmonary artery branches in one dog, is considered significant, because this finding has been reported only in cat In the liver, congestion, intravascular coagulation in the portal system and fibrosis were found. The severity of hepatic lesions was not correlated with the number of adult heartworms found in the posterior vena cava. The kidneys showed mild to moderate membranoproliferative glomerulonephritis and intravenus blood coagulation.